The Association Between Body Mass Index and Gender Role Stress Among Young Hungarian Males - Susánszky, Anna; Döbrössy, Bence (European Journal of Mental Health, 2019)
According to literature references, Body Mass Index (BMI), the quality of sexual life, sexual activity, and satisfaction with sexual life are closely associated. However, we found no research dealing with the relation of gender role stress to the above-mentioned factors in our review of the literature. That is why we chose to focus our research on the association of BMI and gender role stress of young Hungarian adult men. Our data is from the ‘Hungarostudy 2013’ (SUSÁNSZKY & SZÉKELY 2013) national representative survey (N = 2000) of which 298 18–35-year-old men belonged to the subsample researched. Besides socio-demographic data, we used data on height, weight, selfrated health status, the WHO (World Health Organization) Well-Being Index, the Illness Intrusiveness Rating Scale and the short form of Beck Depression Inventory. The Male Gender Role Stress Scale (MGRS) was used to measure gender role stress.Our results demonstrate that overweight and obesity play a significant role in the development of gender role stress. Young overweight and obese men in our sample were much more likely to report high gender role stress (OR = 1.67) and within this, sexual performance related stress (OR = 1.76) and sexual arousal related stress (OR = 3.15) than men with normal BMI.As our research was aimed at investigating social expectations measurable in terms of gender role stress and not with real sexual dysfunctions per se, our results indicate that even male gender role expectations, more precisely, sexual performance related expectations, may cause considerable stress for overweight/obese men.